“Trans-gredindo” barreiras: identidade trans e sua inserção na segurança pública e Forças Armadas - Melo, Márcio Helder (2022)
Initially, it should be noted that Public Security and the Armed Forces still contribute to the maintenance of a very strong sexist and sexist culture in Brazil. However, in the opposite direction of this oppressive movement, we come across cases of trans men and women who, after being inserted in the aforementioned institutions, in an act, above all of courage, decided to adapt their bodies to the gender to which they identify. The present study, although embryonic, has the general objective of analyzing the insertion of transgender people in the Public Security System and Armed Forces, from the perspective of Sexual Rights as Human Rights, resulting in public policy prospecting for this portion of the population, to that we can have concrete and uniform legal support on the matter. As specific objectives, we seek to understand the concept of gender and its interlocution with Queer theory; reflect on the historical process related to transphobic violence; analyze the legal framework regarding the admissibility of trans people in these bodies and the implementation of resources that help access to LGBTQIA+ Human Rights; as well as, to describe and analyze the experiences faced by the transgender population who changed their gender after being inserted in the scope of the institutions that make up the public security forces. In the methodological field, a qualitative approach was chosen, divided into three stages: literature review, document analysis and field research. At the end of the study, we will analyze the results of the research, comparing them with the theories studied, in a sociological perspective, of Human Rights and Law with the purpose of promoting applied research in this field of activity, aiming, above all, to contribute to the implementation and elaboration of public policies aimed at guaranteeing the rights of transgender people in the Public Security System and the Armed Forces.